Hookworm Secreted Extracellular Vesicles Interact With Host Cells and Prevent Inducible Colitis in Mice - Eichenberger, Ramon M.; Ryan, Stephanie; Jones, Linda; Buitrago, Geraldine; Polster, Ramona; Montes de Oca, Marcela; Zuvelek, Jennifer; Giacomin, Paul R.; Dent, Lindsay A.; Engwerda, Christian R.; Field, Matthew A.; Sotillo, Javier; et al. (Frontiers in Immunology, 2018)
Gastrointestinal (GI) parasites, hookworms in particular, have evolved to cause minimal harm to their hosts, allowing them to establish chronic infections. This is mediated by creating an immunoregulatory environment. Indeed, hookworms are such potent suppressors of inflammation that they have been used in clinical trials to treat inflammatory bowel diseases (IBD) and coeliac disease. Since the recent description of helminths (worms) secreting extracellular vesicles (EVs), exosome-like EVs from different helminths have been characterised and their salient roles in parasite-host interactions have been highlighted. Here, we analyse EVs from the rodent parasite Nippostrongylus brasiliensis, which has been used as a model for human hookworm infection. N. brasiliensis EVs are actively internalised by mouse gut organoids, indicating a role in driving parasitism. We used proteomics and RNA Seq to profile the molecular composition of N. brasiliensis EVs. We identified 81 proteins, including proteins frequently present in exosomes (like tetraspanin, enolase, 14-3-3 protein and heat shock proteins), and 27 sperm-coating protein (SCP)-like extracellular proteins. RNA-Seq analysis revealed 52 miRNA species, many of which putatively map to mouse genes involved in regulation of inflammation. To determine whether GI nematode EVs had immunomodulatory properties, we assessed their potential to suppress gastrointestinal inflammation in a mouse model of inducible chemical colitis. EVs from N. brasiliensis but not those from the whipworm Trichuris muris or control vesicles from grapes protected against colitic inflammation in the gut of mice that received a single intra-peritoneal injection of EVs. Key cytokines associated with colitic pathology (IL-6, IL-1 , IFN , IL-17a) were significantly suppressed in colon tissues from EV-treated mice. In contrast, high levels of the anti-inflammatory cytokine IL-10 were detected in N. brasiliensis EV-treated mice. Proteins and miRNAs contained within helminth EVs hold great potential application in development of drugs to treat helminth infections as well as chronic non-infectious diseases resulting from a dysregulated immune system, such as inflammatory bowel diseases.